Development of high frequency pMUT based on sputtered PZT - Lim, Un Hyun; Yoo, Jin Hee; Kondalkar, Vijay; Lee, Keekeun (Journal of Electrical Engineering and Technology, 2018)
A new type of piezoelectric micromachined ultrasonic transducer (pMUT) with high resonant frequency was developed by using a thin lead zirconate titanate (PZT) as an insulation layer on a floating 10 µm silicon membrane. The PZT insulation layer facilitated acoustic impedance matching at active pMUT, leading to a high performance in the acoustic conversion property compared with the transducer using SiO2 insulation layer. The fabricated ultrasonic devices were wirelessly measured by connecting two identical acoustic transducers to two separate ports in a single network analyzer simultaneously. The acoustic wave emitted from a transducer induced a 3.16 µW on the other side of the transducer at a distance of 2 cm. The transducer performances in terms of device diameters, PZT thickness, annealings, and different DC polings, etc. were investigated. COMSOL simulation was also performed to predict the device performances prior to fabrication. Based on the COMSOL simulation, the device was fabricated and the results were compared.
Keywords: COMSOL; Device performance; High frequency HF; Insulation layers; Piezoelectric micromachined ultrasonic transducer (PMUT); pMUT; Silicon membranes; COMSOL; High resonant frequency; pMUT; PZT; Ultrasonic transducer